2020
DOI: 10.1101/2020.05.26.20114033
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Continuous Electroencephalography (cEEG) Characteristics and Acute Symptomatic Seizures in COVID-19 Patients

Abstract: Background: Neurological manifestations of COVID-19 have only recently been described, with a paucity of literature reporting the potential relationship between COVID-19 and acute symptomatic seizures. Two prior studies found no clinical or electrographic seizures in their cohorts of COVID-19 patients with altered mental status (AMS) and clinical seizure-like events (SLEs). Methods: In this retrospective cohort study, 22 critically-ill COVID-19 patients above the age of 18 years who underwent EEG (electroence… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…26 This study also reported a variety of other EEG findings, including continuous slowing, generalized rhythmic activity, and generalized periodic discharges. 26 These studies support the high incidence of encephalopathy in hospitalized patients with COVID-19 and the presence of acute symptomatic seizures from an underlying metabolic or toxic process or primary CNS insult as a complication of COVID-19.…”
Section: Acute Necrotizing Hemorrhagic Encephalopathymentioning
confidence: 61%
See 2 more Smart Citations
“…26 This study also reported a variety of other EEG findings, including continuous slowing, generalized rhythmic activity, and generalized periodic discharges. 26 These studies support the high incidence of encephalopathy in hospitalized patients with COVID-19 and the presence of acute symptomatic seizures from an underlying metabolic or toxic process or primary CNS insult as a complication of COVID-19.…”
Section: Acute Necrotizing Hemorrhagic Encephalopathymentioning
confidence: 61%
“…23 24 Two retrospective studies have described electroencephalogram (EEG) patterns seen in patients with acute COVID-19. 25,26 One study reported frequent sporadic interictal epileptiform discharges in 22 patients with COVID-19 using mostly continuous 8-channel EEGs; 25 however, this finding was not supported by the other study, which used standard 21-channel EEGs. 26 This study also reported a variety of other EEG findings, including continuous slowing, generalized rhythmic activity, and generalized periodic discharges.…”
Section: Acute Necrotizing Hemorrhagic Encephalopathymentioning
confidence: 95%
See 1 more Smart Citation
“…Subsequent to our report, case series of COVID-19-positive patients with EEG studies (n = 13-111 each) have been published by independent groups; yet, none has incorporated COVID-19-negative patient populations exhibiting similar presentations. Among COVID-19-positive patients, the reported rates of EDs in these recently published studies varied between 0% and 38% [3][4][5][6][7][8][9][10] ; our reported 40.9% rate falls at the higher end of the spectrum. Such a spread of rates of epileptiform EEGs among small-or moderate-scale case series from different institutions exemplifies how differences in inclusion criteria, study design, patient enrollment and demographics, and clinical history may alter outcomes.…”
mentioning
confidence: 63%
“…38 Epileptiform abnormalities are detected in COVID-19 patients with encephalopathy. 39 However, it is still unclear whether COVID-19 infection is directly responsible for seizures and if epileptiform activity affects outcome in these patients.…”
Section: Neurological Manifestations Of Covid-19mentioning
confidence: 99%